Pendekatan Theory of Planned Behaviour dalam Rekayasa Perilaku Penggunaan Informasi Akuntansi Manajemen pada UMKM - Aprieza Puspita Zandra, Rosy; Handayani Soedarso, Elvyra; Prasetya, Rizky; Miharso, Apit (Journal of Accounting and Finance Management, 2024)
The use of management accounting information by micro, small and medium enterprises (MSMEs) is often still limited. This is due to the perception that financial recording is complicated and does not provide direct benefits. This research aims to determine the intentions of business actors in Tulusbesar Village in using management accounting information after receiving intervention in the form of training and mentoring. The method used is the Correlational Study with Intervention approach with the framework of the Theory of Planned Behavior. Data was collected through a questionnaire that measured three main variables, namely attitudes, subjective norms, and behavioral control. The research results show that these three variables have an almost equal contribution to business actors' intentions, with attitudes contributing 33.9 percent, subjective norms 33.3 percent, and behavioral control 32.6 percent. Interventions in the form of training and mentoring increase respondents' positive perceptions of accounting and strengthen social support and self-confidence in implementing financial records. The conclusion of this research is that positive attitudes, supportive social norms, and an adequate sense of control jointly influence the intention and behavior of using accounting information. Further mentoring programs and collaboration with the business community are recommended so that the implementation of accounting among MSMEs is more optimal.